2007
DOI: 10.1177/1043659606294193
|View full text |Cite
|
Sign up to set email alerts
|

Iron Deficiency Anemia (IDA) Perceptions and Dietary Iron Intake Among Young Women and Pregnant Women in Jordan

Abstract: To determine Iron Deficiency Anemia (IDA) perceptions and iron dietary practices of Jordanian female students and pregnant women, a descriptive quantitative questionnaire was administered to 271 participants: 206 female students and 65 pregnant women. This pilot study found that most participants can identify foods containing iron, but lack appropriate iron intake, because of eating habits and finances; more than 50% report daily symptoms of IDA, including dizziness, fatigue, depression, headaches, and loss of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
14
1

Year Published

2009
2009
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 20 publications
(26 reference statements)
2
14
1
Order By: Relevance
“…Our finding that the prevalence of anemia among pregnant women increased with lower level of education confirmed the report by Abel et al [18] . Other researchers reported that there were no statistically significant differences in iron-deficiency anemia and iron-related dietary practices based on education, and relatively few differences based on where participants live, their available financial resources, or their position (pregnant women or young women) [19] . Bondevik et al [20] found that the risk of anemia increased with the duration of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Our finding that the prevalence of anemia among pregnant women increased with lower level of education confirmed the report by Abel et al [18] . Other researchers reported that there were no statistically significant differences in iron-deficiency anemia and iron-related dietary practices based on education, and relatively few differences based on where participants live, their available financial resources, or their position (pregnant women or young women) [19] . Bondevik et al [20] found that the risk of anemia increased with the duration of pregnancy.…”
Section: Discussionmentioning
confidence: 99%
“…Other disorders, such as thalassemia or chronic liver disease, or environmental factors, such as dietary excess or transfusional overload, may also contribute to high levels of biological Fe (Kohgo et al 2008). Typically, however, Fe overload is less common than Fe deficiency, which may affect as many as two billion people world wide (WHO 2003) and results in anemic disease states (Jarrah et al 2007;Skalicky et al 2006;Toteja et al 2006;Zhou et al 2006). As a result, Mn and Fe metabolism, as well as that of numerous other metals, is highly regulated at multiple levels (Jensen et al 2009;KaismanElbaz et al 2009;Lee and Beutler 2009;Miyayama et al 2009;Rondon et al 2008) to reduce the risk that either too much or too little of the metal poses to normal cellular homeostasis and function.…”
Section: Mn and Fe Transportmentioning
confidence: 98%
“…In their quantitative study of Jordanian women' perceptions of anemia, the authors found that there were no differences in perceptions based on education (9) .…”
Section: Introductionmentioning
confidence: 98%